Pelatihan Pengajaran Bahasa Inggris untuk Guru Sekolah Dasar di Makassar: Pendekatan Kolaboratif - Hasnani, Hasnani; Sukmawati, Sukmawati (Yayasan Habiburrahman Jamalu Bina Ummat, 2025)
This community service activity aims to improve the competence of elementary school teachers in Makassar in teaching English through a collaborative approach. This training is designed to equip teachers with innovative, communicative-based teaching strategies that are in accordance with the needs of elementary school students. The methods used in this training include interactive workshops, group discussions, and teaching simulations that allow participants to directly practice the material they have learned. In addition, a collaborative approach is applied by involving teachers in sharing experiences and preparing joint lesson plans. The results of the activity show that this training has a positive impact on teachers' understanding of effective English teaching methods. Participants responded positively to the material presented and felt more confident in implementing new strategies in the classroom. In addition, collaboration between teachers also increased, creating a learning community that supports continuous professional development. In conclusion, this training has succeeded in making a real contribution to improving the quality of English teaching in elementary schools. It is hoped that similar activities can continue to be carried out to support teacher professionalism and improve the quality of English education at the elementary level.